Analisis Keterampilan Guru Kelas V Mengadakan Variasi dalam Pembelajaran Tematik di SDN Ngargoloka - Hermayani, Nitasari Septi; Winarti, Puji; Sri Legowo, Yogi Ageng (Faculty of Teacher Training and Education of Undaris, 2024)
Variation skills in teaching are important for teachers. Therefore, the focus of this research is to analyze the skills of teachers to make variations which include variations in teaching styles, media variations, and variations in interaction patterns in class V in thematic learning at SDN Ngargoloka, Gladagsari District, Boyolali Regency. The type of research used is qualitative and the research data is analyzed descriptively. From the data analysis, it was found that the fifth grade teacher already had the skills to make variations in learning. The variety of teaching styles of fifth grade teachers is said to be good and varied, because almost all indicators of teaching style variations have been implemented. The teacher's skills in making variations that have been owned such as voice variations, silence, gestures, concentration of attention, eye contact, and the help of learning media tools used such as maps, globes, source books, LCD, and HandPhone and interaction patterns. The obstacles experienced by teachers in applying the skills of making variations are that teachers experience confusion in explaining thematic material that combines several materials at one time, besides that the character of different students, such as when the teacher gives time for discussion, only a few students do it and the others are busy themselves. this happens because schools have limited facilities and infrastructure such as teaching aids and learning media, so this limitation makes teachers when explaining thematic material without the help of media become abstract for students and it is easier to understand the material presented by the teacher if the teacher explains the material using tools. This will certainly hinder learning.Keywords: analysis, teacher skills, teacher variation, thematic learning thematic learning